2009
DOI: 10.1002/stem.178
|View full text |Cite
|
Sign up to set email alerts
|

3D Timelapse Analysis of Muscle Satellite Cell Motility

Abstract: Skeletal muscle repair and regeneration requires the activity of satellite cells, a population of myogenic stem cells scattered throughout the tissue and activated to proliferate and differentiate in response to myotrauma or disease. While it seems likely that satellite cells would need to navigate local muscle tissue to reach damaged areas, relatively little data on such motility exist, and most studies have been with immortalized cell lines. We find that primary satellite cells are significantly more motile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(147 citation statements)
references
References 70 publications
10
135
0
2
Order By: Relevance
“…By culturing individual myofibers, satellite cell heterogeneity with respect to myofiber, muscle type or regenerative potential has been addressed 15 . Elaborate studies using live imaging of single cultured fibers allowed for the gaining information on satellite cell migration pattern 16 . The acquisition of quantitative data is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…By culturing individual myofibers, satellite cell heterogeneity with respect to myofiber, muscle type or regenerative potential has been addressed 15 . Elaborate studies using live imaging of single cultured fibers allowed for the gaining information on satellite cell migration pattern 16 . The acquisition of quantitative data is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that activated primary satellite cells are highly motile in the context of their native substrate (the surface of the myofiber), moving up to 2.4 cm in 24 hours (Siegel et al, 2009). The same study found that activated satellite cells express mRNAs encoding multiple examples of classical guidance pathway ligands and receptors (Ephs, ephrins, semaphorins, plexins, neuropilins and Robos).…”
Section: Introductionmentioning
confidence: 94%
“…However once they have emerged onto the muscle fiber, migration, one of the key activities undertaken by the stem cells is severely limited by the absence of glycolytic activity [7,20]. Our results show that this process must be highly energy dependent since the cells unable to fully undertake glycolysis decrease their migration rate by over 50%.…”
Section: Discussionmentioning
confidence: 85%